PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN WORDWALL UNTUK MENINGKATKAN MINAT BELAJAR MATEMATIKA SISWA KELAS IV SD SWASTA IT CEMARA ISLAMI PLUS - Putri, Fanny Landari; Anshor, Arrini Shabrina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The objective of the research was to develop a learning media assisted by Wordwall to improve the interest in learning mathematics of grade IV elementary school students. This research was a development research (Research and Development) using the ADDIE development model and procedures consisting of 5 stages, namely (Analysis, Design, Development, Implementation, and Evaluation). The data collection techniques used in this research was observation, interviews, questionnaires and documentation. The instruments and data analysis techniques used in this research were questionnaires given to several expert reviewers, namely material expert reviewers, media expert reviewers, teacher responses, students’ responses and students’ mathematics learning interest responses. The validation score obtained from the material expert reviewers was 85%. Media experts were 100%. Teacher responses were 93.75%. Students’ responses were 92.88%. Students’ mathematics learning interest responses were 91.98%. From these scores, it can be said that the Word Wall-assisted learning media to increase the interest in learning mathematics of grade IV elementary school students that was developed was “very valid” and “very feasible’ to be used in the learning process